2018
DOI: 10.14196/mjiri.32.56
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing decision making for healthcare services outsourcing: A review and Delphi study

Abstract: Background: Outsourcing is considered as one of the tools for organizational development and promotion of productivity by managers. In recent years, outsourcing of healthcare services has become significant. The aim of this study was to identify the most important factors influencing the decision making of outsourcing healthcare services. Methods: This study is a combined study. First, the literature was examined to identify the factors influencing decision making for outsourcing. Then, with the aim of consen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 21 publications
(39 reference statements)
1
30
0
Order By: Relevance
“…The Bartlett's Test of Sphericity also serves to test whether or not questionnaire variables are correlated to the target population for which the tested tool is intended. Thus, it is indicated if the factorial model is adequate (15) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Bartlett's Test of Sphericity also serves to test whether or not questionnaire variables are correlated to the target population for which the tested tool is intended. Thus, it is indicated if the factorial model is adequate (15) .…”
Section: Discussionmentioning
confidence: 99%
“…In the correlation matrix, it is recommended that only items with coefficients equal to or greater than 0.4 remain in the scale. Scree plot items have to be considered all above 1, with a variance of at least 60.0% (15) . The model predicted by EFA was adjusted by FCA, as it allows the correction of the exploratory model, and leads to a greater certainty of hypotheses (12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a systematic review, 29 subfactors affecting decision making on e-health-related services were identified under four main factors: strategic, quality, management and technological. 2 In contrast, influencing factors were analysed based on their priority among healthcare professionals, health information professionals and managers, who identified that service-related factors were preferred by healthcare professionals while operational factors were preferred by managers. 19 However, these studies have undermined the influence of sociocultural and demographic factors, such as population demographics, religion, social norms and lifestyles, 20 , 21 which may also influence decision making on e-health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 However, the complexity of healthcare infrastructure, the competitive economy of healthcare operations and services and the need to deliver high-quality services can lead to continuous development and reengineering of healthcare operations, strategies, goals and managerial approaches. 2 The coronavirus disease 2019 (COVID-19) pandemic has strained the healthcare systems in many countries, affecting individuals suffering from other diseases due to the limitations in healthcare resources, finance and operations management. 3–5 In addition, the confirmed COVID-19 cases have been steadily increasing since it emerged in China in December 2019.…”
Section: Introductionmentioning
confidence: 99%